2020
DOI: 10.2337/db20-0669
|View full text |Cite
|
Sign up to set email alerts
|

Expression of ACE2, the SARS-CoV-2 Receptor, in Lung Tissue of Patients With Type 2 Diabetes

Abstract: Increased expression of pulmonary ACE2, the SARS-CoV-2 receptor, could contribute to increased infectivity of COVID-19 in subjects with diabetes, but ACE2 expression has not been studied in lung tissue of subjects with diabetes. We therefore studied ACE2 mRNA and protein expression in lung tissue samples of patients with and without diabetes that were collected between 2002 and 2020 from patients undergoing lobectomy for lung tumors. For RT-PCR analyses, samples from 15 subjects with diabetes were compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 53 publications
6
47
2
1
Order By: Relevance
“…As a positive control for our immunohistochemistry method and ACE2 antibodies adopted, we evaluated FFPE lung tissue sections. As previously shown (7,41,42), we observed scattered positive cells (putatively AT2 pneumocytes) in the alveolar epithelium both using MAB933 and Ab 15348 ( Figure S3A and S3B ). In contrast, we did not observe any signal using Ab108252 ( Figure S3C ).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…As a positive control for our immunohistochemistry method and ACE2 antibodies adopted, we evaluated FFPE lung tissue sections. As previously shown (7,41,42), we observed scattered positive cells (putatively AT2 pneumocytes) in the alveolar epithelium both using MAB933 and Ab 15348 ( Figure S3A and S3B ). In contrast, we did not observe any signal using Ab108252 ( Figure S3C ).…”
Section: Resultssupporting
confidence: 86%
“…On the contrary, by using two different antibodies (MAB933 and Ab15348) - which can recognize the C-terminal domain shared between short- and long-ACE2 - we obtained clear and concordant results, with identification of ACE2 in pancreatic islet endocrine cells in addition to the microvasculature. As a positive control for the antibodies and our IHC procedure, MAB933 and Ab15348 were also tested in FFPE lung tissue sections, showing overlapping results with previously published studies (7,41,42).…”
Section: Discussionsupporting
confidence: 74%
“…On the contrary, by using two different antibodies (MAB933 and Ab15348)-which can recognize the C-terminal domain shared between short-and long-ACE2-we obtained clear and concordant results, with identification of ACE2 in pancreatic islet endocrine cells in addition to the microvasculature. As a positive control for the antibodies and our IHC procedure, MAB933 and Ab15348 were also tested in FFPE lung tissue sections, showing overlapping results with previously published studies (7,41,42).…”
Section: Discussionsupporting
confidence: 72%
“…Recent data investigating ACE2 expression in lung tissue of patients with type 2 diabetes showed that protein levels of ACE2 were significantly increased in both alveolar tissue and bronchial epithelium of patients with diabetes. 27 Opposite to our predictions, a single study, on a limited number of human gingival samples, showed weaker ACE2 immunostaining in periodontitis compared with healthy gingival samples. 28 Caution must be taken regarding the interpretation of this result since Descamps et al 22 suggested that lack of ACE2 immunostaining in oral tissues could be explained by the cleavage of ACE2 receptor by disintegrin and metalloproteinase (ADAM 17), activity of which enhances in inflammatory states, 29 such as periodontitis.…”
Section: Gene Interaction Networkcontrasting
confidence: 47%